Acanthamoeba Keratitis: A 12-Year Experience Covering a Wide Spectrum of Presentations, Diagnoses, and Outcomes - Michael A. Page; William D. Mathers (Journal of Ophthalmology)
Purpose. To review characteristics of confocal microscopy, clinical presentation, and clinical outcome in 372 cases of Acanthamoeba keratitis (AK) from 1999 to 2011. Methods. A retrospective case review was performed on 372 cases of AK diagnosed by confocal microscopy (CFM) at a single institution in Portland, Oregon, from 1999 to 2011. A numbered grading system was devised for describing the relative microscopic severity of the AK infections detected. Results. “grade 1,” 94 as “grade 2,” 40 as “grade 3,” and 62 as “grade 4.” Peak incidences occurred during 2000–2002 and 2005–2007. Seasonal variation was noted, with a peak during summer months. For the 231 cases with complete records, 64% indicated a history of soft contact lens use. Nine progressed to multiple failed penetrating keratoplasties (PKPs) or enucleation. Conclusion. We report an average of 31 new cases of AK per year from 1999 to 2011. This figure equates to 10.3 new cases/1,000,000/year for the Portland metropolitan area. Patients diagnosed with AK exhibited a wide spectrum of clinical and microscopic characteristics. Soft contact lens use remained the single largest risk factor.